Liquid Biospy: Noninvasive Diagnosis and Molecular Phenotyping of Breast Cancer through Microbead‐Assisted Flow Cytometry Detection of Tumor‐Derived Extracellular Vesicles (Small Methods 11/2018). Issue 11 (5th November 2018) - Li, Wenzhe; Shao, Bin; Liu, Changliang; Wang, Huayi; Zheng, Wangshu; Kong, Weiyao; Liu, Xiaoran; Xu, Guobin; Wang, Chen; Li, Huiping; Zhu, Ling; Yang, Yanlian
Abstract : Extracellular vesicle‐based diagnosis and molecular phenotyping provide great help for precise diagnosis and treatment of cancer. In article1800122, Huiping Li, Ling Zhu, Yanlian Yang, and co‐workers establish an assessment for the detection and molecular phenotyping of serum extracellular vesicles using microbead‐assisted flow cytometry. Molecular phenotyping is facilitated by immunostaining of important biomarkers for diagnosis, prognosis, and therapeutic evaluation on nanosized extracellular vesicles that are enriched on microsized aldehyde latex beads. This method shows great efficacy in diagnosing breast cancer and holds great potential as a surrogate for the invasive tissue‐based molecular phenotyping.